2019
DOI: 10.4097/kja.d.18.00121
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the clinical performance of airway management with the i-gel® and laryngeal mask airway SupremeTM in geriatric patients: a prospective and randomized study

Abstract: Background Geriatric patients are susceptible to respiratory and hemodynamic adverse events during endotracheal intubation and extubation due to anatomic and physiological changes with aging. Supraglottic airway devices (SADs) provide reduced airway morbidity and increased hemodynamic stability in adults. However, studies that have compared the clinical performance of SADs in geriatric patients are limited. Therefore, we evaluated the clinical performance of airway management with i-gel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…Patients who received iGel as an airway device compared with laryngeal mask airways were found to have a slightly higher incidence of hiccup although these were not found to be statistically significant [ 27 ]. There was also a study showing traditional laryngeal mask airway induces more gastric insufflation, though they did not show the incidence of hiccup [ 28 ].…”
Section: Laryngeal Mask Airway-related Hiccupmentioning
confidence: 99%
“…Patients who received iGel as an airway device compared with laryngeal mask airways were found to have a slightly higher incidence of hiccup although these were not found to be statistically significant [ 27 ]. There was also a study showing traditional laryngeal mask airway induces more gastric insufflation, though they did not show the incidence of hiccup [ 28 ].…”
Section: Laryngeal Mask Airway-related Hiccupmentioning
confidence: 99%
“…In addition, while the studies included in this meta-analysis covered a wide range of age groups from 18 to 80 years, none of them considered the influence of patient characteristics (12) . It is known that OSP may be affected by a variety of factors, such as cuff pressure, leak detection method, and age releated anatomic changes (13) . In our study, we did not use neuromusculer blocking (NMB) agent and swelling of the cuff of p-LMA may have caused malposition in these geriatric population.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we did not use neuromusculer blocking (NMB) agent and swelling of the cuff of p-LMA may have caused malposition in these geriatric population. In a study that compares the clinical performance of i-gel and LMA supreme (sLMA) in elderly, authors found that OSP was higher in i-gel than sLMA both immediately after placement and at the end of the operation (13) . Similarly, in our study, we found that the OSP measured in the i-gel group was higher than other SADs immediately after insertion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] The ability to predict risk factors for LVF is crucial because of the negative consequences of LVF that include chronic back pain, related functional disability, kyphosis, and height loss, all of which have major impacts on a patient's quality-of-life; as well as the associated increases in morbidity and mortalitiy. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Analysis of bone mineral density (BMD) using dual-energy X-ray absorptiometry (DEXA) is the most commonly used index of bone power, and a low BMD is the most important risk factor for LVF prediction. [21][22][23][24] But, almost 50% of LVF occurs in patients with BMD above the World Health Organization (WHO) diagnosis threshold of osteoporosis (T-score#2.5).…”
Section: Introductionmentioning
confidence: 99%